2002
DOI: 10.1381/096089202762252307
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and Postoperative Psychological Characteristics in Morbidly Obese Patients

Abstract: Pre-existing psychopathology was more obvious among females, and improved significantly following successful weight loss 1 year postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…Cassin et al [40] found similar BMI (48 kg/m 2 ) and a mean age (44 years), as well as a high proportion of female gender (77%). The elevated proportion of female gender, associated with higher depression severity, has been shown in various studies [37,40,49,50] and could be confirmed in our analysis. However, BMI was not correlated to depression severity or somatization in our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Cassin et al [40] found similar BMI (48 kg/m 2 ) and a mean age (44 years), as well as a high proportion of female gender (77%). The elevated proportion of female gender, associated with higher depression severity, has been shown in various studies [37,40,49,50] and could be confirmed in our analysis. However, BMI was not correlated to depression severity or somatization in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, socioeconomic and culture-bound heterogeneity of the sample could have influenced subjective rating of obesity and psychological burden [58]. Another possible explanation could be an adaptation process of obese patients, leading to neutral subjective rating of objectively severe restraints and impairments [49].…”
Section: Limitationsmentioning
confidence: 99%
“…Depression and dysphoria appear to be consequences of being obese [17] . In the study of Papageorgiou et al [18] , a preponderance of female compared to male obese patients was found regarding depression, interpersonal sensitivity, paranoid ideation, somatization, obsessive-compulsive behavior, anxiety and hostility. Concerning family relationships morbidly obese patients more frequently had a history of parental loss, parental alcoholism, marital family dysfunction in their own lives and dissatisfying sexual relationships [19] .…”
Section: Psychopathologymentioning
confidence: 92%
“…Obesity discrimination, social isolation, and stigma experiences [7,8] start in the earliest social contacts [9], and this prejudice may contribute to depression, eating disorders, body image disturbance, and other suffering [2,10,11].…”
Section: Introductionmentioning
confidence: 99%